Non-volitional assessment of skeletal muscle strength in patients with chronic obstructive pulmonary disease. Issue 8 (28th July 2003) - Man, W D-C; Soliman, M G G; Nikoletou, D; Harris, M L; Rafferty, G F; Mustfa, N; Polkey, M I; Moxham, J
Abstract : Background: Although quadriceps weakness is well recognised in chronic obstructive pulmonary disease (COPD), the aetiology remains unknown. In disabled patients the quadriceps is a particularly underused muscle and may not reflect skeletal muscle function as a whole. Loss of muscle function is likely to be equally distributed if the underlying pathology is a systemic abnormality. Conversely, if deconditioning and disuse are the principal aetiological factors, weakness would be most marked in the lower limb muscles. Methods: The non-volitional technique of supramaximal magnetic stimulation was used to assess twitch tensions of the adductor pollicis, quadriceps, and diaphragm muscles (TwAP, TwQ, and TwPdi) in 22 stable non-weight losing COPD patients and 18 elderly controls. Results: Mean (SD) TwQ tension was reduced in the COPD patients (7.1 (2.2) kg v 10.0 (2.7) kg; 95% confidence intervals (CI) −4.4 to −1.4; p<0.001). Neither TwAP nor TwPdi (when corrected for lung volume) differed significantly between patients and controls (mean (SD) TwAP 6.52 (1.90) N for COPD patients and 6.80 (1.99) N for controls (95% CI −1.5 to 0.97, p=0.65; TwPdi 23.0 (5.6) cm H2 O for COPD patients and 23.5 (5.2) cm H2 O for controls (95% CI −4.5 to 3.5, p=0.81). Conclusions: The strength of the adductor pollicis muscle (and the diaphragm) is normal in patients with stable COPD whereas quadriceps strength is substantially reduced. Disuse may be the principal factor in the development of skeletal muscle weakness in COPD, but a systemic process preferentially affecting the proximal muscles cannot be excluded.